The sedges and grasses of Gautambudhnagar (Noida) U.P. India - Chaudhary, Shalu; Gupta, A K; Kumar, Lalit (International Multidisciplinary Research Journal, 2012)
The present study is the result of two years (April 2005-April 2007) of extensive survey and exploration of sedges and grasses of Gautambudh Nagar. A total number of 95 species of Cyperaceae and Gramineae (Poaceae) have been collected from this area. Out of 95 species of these two families belonging to 68 genera, 65 species belong to Gramineae (Poaceae) and 30 species belong to Cyperaceae. There are two plants of Cyperaceae and Gramineae (Poaceae) respectively: Eleocharis capitata R. Br. and Isachne albens Trin., which have been reported for the first time from this area.